2020
DOI: 10.1111/pai.13238
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of allergy to pistachio in children allergic to cashew nut

Abstract: Background: Cashew nut (CN) allergy prevalence has increased over the last few years. In children allergic to CN, complete avoidance of pistachio is usually recommended, but recent study showed that only one third of children allergic to CN were also allergic to pistachio. The aim of our study was to identify predictive factors of allergy to pistachio in children allergic to CN. Methods: All children who had a positive oral food challenge (OFC) to CN between November 2013 and October 2017 in the Paediatric All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this respect, the sequence similarities observed between the homologous allergens of Anacardiaceae, e.g., between Pis v 1 and Ana o 3 or between Pis v 2 and Ana o 2, account for the high level of cross-reactivity and cross-allergenicity observed between pistachio and cashew. The IgE-binding cross-reactivity the major allergens from pistachio, Pis v 1, Pis v 2 and Pis v 3, share with homologous proteins from peanut, tree nuts and proteins from, sesame, buckwheat, peppercorn or mango, has a clinical incidence and in particular, helps to discriminate between allergies and co-sensitizations [19,22,[70][71][72][73][74][75][76][77][78]. Whereas co-sensitization frequently occurs between pistachio and cashew, it is clinically relevant in only one-third of cases [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the sequence similarities observed between the homologous allergens of Anacardiaceae, e.g., between Pis v 1 and Ana o 3 or between Pis v 2 and Ana o 2, account for the high level of cross-reactivity and cross-allergenicity observed between pistachio and cashew. The IgE-binding cross-reactivity the major allergens from pistachio, Pis v 1, Pis v 2 and Pis v 3, share with homologous proteins from peanut, tree nuts and proteins from, sesame, buckwheat, peppercorn or mango, has a clinical incidence and in particular, helps to discriminate between allergies and co-sensitizations [19,22,[70][71][72][73][74][75][76][77][78]. Whereas co-sensitization frequently occurs between pistachio and cashew, it is clinically relevant in only one-third of cases [72].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas co-sensitization frequently occurs between pistachio and cashew, it is clinically relevant in only one-third of cases [72]. However, skin prick tests (SPT) performed on French children indicated that a low reaction dose to cashew in cashew-allergic children would be a predictive factor of allergy to pistachio [78]. Accordingly, oral food challenge to pistachio should be avoided in cashew-allergic children exhibiting a low reaction dose to cashew nut.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assessed the rate of anaphylaxis to very low (≤upper 95th CI for the ED 05 ) 6 levels of allergen consumption at FC to cashew 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ( Table E1 , available in this article’s Online Repository at www.jaci-inpractice.org ), hazelnut 27 , 28 , 29 , 30 , 31 , 37 , 38 , 39 , 40 ( Table E2 , available in this article’s Online Repository at www.jaci-inpractice.org ), and walnut 29 , 30 , 41 , 42 , 43 ( Table E3 , available in this article’s Online Repository at www.jaci-inpractice.org ) reported in the literature, and undertook a meta-analysis ( Figures E1-E3 , available in this article’s Online Repository at www.jaci-inpractice.org ). These data are summarized in Table IV .…”
Section: Tree Nutsmentioning
confidence: 99%
“…Thus, the fear for a life-threatening allergic reaction after accidental exposure to an allergen has a significant impact on the quality of life of both patients and their families 1,3 . Among tree nuts, the prevalence of cashew allergy is increasing, being reported to cause even more severe anaphylactic reactions than peanut allergy 1,4 . Cashew (CN) and pistachio share a phylogenetic origin and are members of the Anacardiaceae family.…”
mentioning
confidence: 99%